Association of sarcopenia and muscle mass with both peripheral neuropathy and nerve function in patients with type 2 diabetes. (April 2020) - Zhang, Yongze; Shen, Ximei; He, Lanlan; Zhao, Fengying; Yan, Sunjie
Highlights: Sarcopenia and Peripheral neuropathy. Muscle mass Change and Nerve function. Cross-sectional study and Follow-up study. Abstract: Aim: This study aimed to investigate the association of sarcopenia and muscle mass with both peripheral neuropathy and nerve function in type 2 diabetes mellitus. Methods: A total of 1794 patients (937 men and 857 women) with type 2 diabetes, with a mean age of 60.22 years, were enrolled for a cross-sectional study; of these, 183 patients were enrolled for a follow-up study with a median follow-up of 2.7 years. All participants underwent nerve conduction studies and muscle mass index (ASM/HT 2 ) measurements. The composite Z scores for the sensory nerve conduction velocity (SCV) and the motor nerve conduction velocity (MCV) were calculated. The changes in ASM/HT 2, SCV, and MCV were calculated from the measurements nearly 2 years apart and classified into three groups: a decrease in ASM/HT 2 of >3%, a minor change within ±3%, and an increase in ASM/HT 2 of >3%. Results: The ASM/HT 2 of men was positively associated with the composite Z scores of MCV and SCV, and sarcopenia highly correlated with DPN after adjusting for confounding factors. The optimal cutoff point for ASM/HT 2 that indicated DPN was 7.09 kg/m 2 . Furthermore, increases in ASM/HT 2 independently predicted a greater benefit of MCV and SCV increment outcomes, whereas a minor change in ASM/HT 2 only significantly associated with lower benefit in terms of SCV increment. However, this phenomenon was not observed in women. Conclusions: Sarcopenia and DPN exhibited a close association. The increased muscle mass improved the partial MCVs and SCVs. However, a sex-related discrepancy was observed in this phenomenon.